2017
DOI: 10.1007/s11095-017-2163-x
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Panel-Based Pharmacogenetic Testing: The Time is Now

Abstract: While recent discoveries have paved the way for the use of genotype-guided prescribing in some clinical environments, significant debate persists among clinicians and researchers about the optimal approach to pharmacogenetic testing in clinical practice. One crucial factor in this debate surrounds the timing and methodology of genotyping, specifically whether genotyping should be performed reactively for targeted genes when a single drug is prescribed, or preemptively using a panel-based approach prior to drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 19 publications
1
69
0
3
Order By: Relevance
“…Additionally, education for providers and materials to assist both the provider and the patient through the testing process, and receiving results, were identified as other areas to address. Previous studies have identified a similar need and various educational resources have been made available online [42,43]. Although this study provides insight into how physicians view the direct access PGx test delivery model, further research will be needed to assess the patients' perspectives of this model, including perceived benefits and challenges.…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, education for providers and materials to assist both the provider and the patient through the testing process, and receiving results, were identified as other areas to address. Previous studies have identified a similar need and various educational resources have been made available online [42,43]. Although this study provides insight into how physicians view the direct access PGx test delivery model, further research will be needed to assess the patients' perspectives of this model, including perceived benefits and challenges.…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 93%
“…Time constraints for providing medications in an emergent scenario make it difficult for patients to utilize PGx testing, which is due to the length of time it requires for the sample to be analyzed and resulted [35]. However, some argue that pre-emptive PGx testing may be a way to mitigate this concern [42]. Physicians also described test cost incurred by the patient (as many insurance companies will not cover testing) as one of the most significant barriers to PGx testing.…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…Therefore, it is critical for every health care provider using pharmacogenomics within the practice understand the nuances of this work and be aware of all available resources as we usher in new practices in regard to patient care. 7 While this is an exciting time for the field of precision health, more work being done by the NIH will hopefully propel us into the next stage of understanding the impact of precision medicine in practice through the creation of the "All of Us" program, which "will enable a new era of medicine in which researchers, health care providers, and patients work together to develop individualized care" (https://allofus.nih.gov/about/ab out-all-us-research-program). By recruiting and analyzing samples from more than 1 million individuals within the United States, this participantengaged and data-driven research may just usher in the next generation of "precision health."…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Perhaps the biggest misconception about pharmacogenomics is that the “answers” provided by testing results are simple, when in fact this is not often the case. Therefore, it is critical for every health care provider using pharmacogenomics within the practice understand the nuances of this work and be aware of all available resources as we usher in new practices in regard to patient care …”
mentioning
confidence: 99%
“…Significant debate persists regarding the optimal timing and methodology of testing for delivering PGx testing in clinical care . Some support a pretherapeutic single gene–drug approach, in which a PGx test of a single relevant gene is ordered once a target drug is prescribed; whereas others advocate for a pre‐emptive panel‐based strategy in which multiple genes are tested simultaneously and saved for later use, in preparation of future prescriptions throughout a patient's lifetime . When combined with a clinical decision support system, the corresponding PGx guideline can be deployed by the clinical decision support system at the point of care, thereby providing clinicians with the necessary information to optimize drug prescribing when a target drug is prescribed.…”
mentioning
confidence: 99%